2021
DOI: 10.3390/ijerph18062825
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Beliefs about Medicines on the Level of Intentional Non-Adherence to the Recommendations of Elderly Patients with Hypertension

Abstract: Background: Non-adherence to pharmaceutical treatment is one of the most common causes of uncontrolled hypertension. Non-adherence may be intentional or unintentional. In the case of intentional non-adherence, it is crucial to understand the reasons behind it. The literature increasingly addresses the issue of beliefs and concerns about medication, but studies on this subject performed in a Polish population of hypertensive patients are still lacking. The aim of the study was to assess the level of intentional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Our findings are in line with previous research showing the influence of beliefs about medicines on intentional non-adherence to treatment of various chronic diseases [ 9 , 30 , 37 ]. Patients with MS who had stronger beliefs that medicines in general are overused by doctors (β = 4.204, p = 0.011) more often displayed intentional non-adherence, which is in line with the results of studies conducted among patients with HIV [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our findings are in line with previous research showing the influence of beliefs about medicines on intentional non-adherence to treatment of various chronic diseases [ 9 , 30 , 37 ]. Patients with MS who had stronger beliefs that medicines in general are overused by doctors (β = 4.204, p = 0.011) more often displayed intentional non-adherence, which is in line with the results of studies conducted among patients with HIV [ 37 ].…”
Section: Discussionsupporting
confidence: 93%
“…According to the Necessity–Concerns Framework, beliefs about the necessity of taking medications and concerns about the potential side effects of medications are key beliefs that influence medication adherence [ 29 ]. Research to date has shown that beliefs about medicines have been shown to be an important factor influencing adherence [ 30 , 31 , 32 , 33 ]. Pust et al [ 28 ] has shown that first-line patients, with less necessity beliefs for treatment, are at risk of being non-adherent patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent systematic reviews and observational studies highlight the relevance of socio-cultural determinants on adherence to pharmacotherapy among patients living with NCDs ( Dhar et al, 2017 ; Niriayo et al, 2018 ; Swihart et al, 2018 ; Shahin et al, 2019 ; Al-Ganmi et al, 2020 ; Park et al, 2020 ; Raza et al, 2020 ; Świątoniowska-Lonc et al, 2021 ); however, the dearth of published literature suggests such awareness in pharmacovigilance processes is yet to be realized. Although poor adherence to pharmacotherapy is a common predictor of adverse drug reactions; the converse is also true ( Gellad et al, 2011 ; Adem et al, 2021 ; Elangwe et al, 2020 ) and therefore enriching pharmacovigilance processes with what is referred to as ‘the patient’s voice’ may facilitate causality analysis of adverse drug reactions ( Simon et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Along the same lines, a meta-analysis [4] analyzing adherence in hospital and community interventions found that healthy eating habits, community support, group intervention, and knowledge of the symptomatology related to the disease being suffered are crucial elements in supporting adherence to treatment. Moreover, individual factors (such as elderly age and treatment utility beliefs) impact treatment non-adherence and affect treatment success in both chronic and acute diseases [5]. It has also been found [1,6] that non-adherence and noncompliance with homework are related to personal variables, such as impulsivity.…”
Section: Introductionmentioning
confidence: 99%